2015
DOI: 10.2135/cropsci2014.03.0255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Onion (Allium cepa L.) Lines and Hybrids Possessing Bs1 for Resistance against Multiple Isolates of Botrytis squamosa

Abstract: Onion (Allium cepa L.) lines resistant to Botrytis leaf blight (BLB) were produced by backcrossing the Bs1 BLB resistance of Allium roylei Stearn into cultivated onion. This study evaluated important issues for the commercial use of BLB‐resistant onions: the relative degree of BLB control possible when Bs1 is homozygous rather than heterozygous, the control achieved against multiple pathogen isolates, and the potential for negative traits associated with transfer of Bs1. Homozygous BLB‐resistant onions tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Our results also demonstrated that resistance to B. squamosa in A. roylei is based on a high level of partial resistance, indicating that plants still can be infected by the pathogen. This is in line with other studies in which Botrytis leaf blight symptoms were also observed in onion plants homozygous for the Bs1 gene [ 10 ]. These plants were obtained after two generations of back-crossing to onion of an interspecific F1 hybrid between onion and A. roylei , followed by three to four generations of selfing.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results also demonstrated that resistance to B. squamosa in A. roylei is based on a high level of partial resistance, indicating that plants still can be infected by the pathogen. This is in line with other studies in which Botrytis leaf blight symptoms were also observed in onion plants homozygous for the Bs1 gene [ 10 ]. These plants were obtained after two generations of back-crossing to onion of an interspecific F1 hybrid between onion and A. roylei , followed by three to four generations of selfing.…”
Section: Discussionsupporting
confidence: 93%
“…These plants were obtained after two generations of back-crossing to onion of an interspecific F1 hybrid between onion and A. roylei , followed by three to four generations of selfing. Under heavy disease pressure, heterozygous plants had levels of BLB symptoms between those of homozygous resistant inbred plants and susceptible controls [ 10 ]. After crossing the interspecific RF hybrid with onion, we found only one CCxRF plant with an infection level similar to A. roylei and RF, whereas all other plants, that we also considered resistant, had higher levels of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations